Genetic diversity of tomato response to heat stress at the QTL and transcriptome levels. (24th August 2021) - Bineau, Estelle; Diouf, Isidore; Carretero, Yolande; Duboscq, Renaud; Bitton, Frédérique; Djari, Anis; Zouine, Mohamed; Causse, Mathilde
SUMMARY: Tomato is a widely cultivated crop, which can grow in many environments. However, temperature above 30°C impairs its reproduction, subsequently impacting fruit yield. We assessed the impact of high‐temperature stress (HS) in two tomato experimental populations, a multi‐parental advanced generation intercross (MAGIC) population and a core‐collection (CC) of small‐fruited tomato accessions. Both populations were evaluated for 11 traits related to yield components, phenology and fruit quality in optimal and HS conditions. HS significantly impacted all traits in both populations, but a few genotypes with stable yield under HS were identified. A plasticity index was computed for each individual to measure the extent of the heat impact for each trait. Quantitative trait loci (QTL) were detected in control and HS conditions as well as for plasticity index. Linkage and genome‐wide association analyses in the MAGIC and CC populations identified a total of 98 and 166 QTLs, respectively. Taking the two populations together, 69 plasticity QTLs (pQTLs) were involved in tomato heat response for 11 traits. The transcriptome changes in the ovary of six genotypes with contrasted responses to HS were studied, and 837 genes differentially expressed according to the conditions were detected. Combined with previous transcriptome studies, these results were used to propose candidate genes for HS response QTLs. Significance Statement: Tomato genotypes tolerant to heat stress were identified in two experimental populations covering a large range of variation grown in control and heat stress conditions. Heat‐response QTLs were mapped for agronomic, fruit set and fruit quality traits. Genes differentially expressed in the ovary under heat and control conditions were identified in three susceptible and three tolerant genotypes. Candidate genes for plasticity QTLs were then proposed.